Incremental Rotary Encoder Accuracy Testing On Ship Rudder Simulation - Arif Rakhman Suharso (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
Incremental rotary encoder is a sensor that can be used to measure the degree of rotation in ship steering simulations. To create a ship steering simulation, Visual Basic software was used to simulate the movement of the rudder and ship. Meanwhile, to obtain incremental rotary encoder reading data, serial communication is used via Universal Serial Bus (USB) media bridged by Arduino which is programmed to convert incremental sensor signals into ASCII signals with a bolt rate of 9600 bps. The aim of this research is to test the accuracy level of the incremental rotary encoder sensor in ship steering simulations using Visual Basic software on commercial ships by using the Solas rule that a ship's rudder must comply when rotated from the midship position to the 35 degree port side position followed by the 35 degree position. starboard side and returning to midship, the rudder movement time was less than 28 seconds. Test results in terms of response speed of the incremental rotary encoder sensor are very good, while in terms of accuracy level for one degree of steering rotation, the result is 4.571 on the Arduino IDE serial monitor reading..